1998
DOI: 10.1111/j.1530-0277.1998.tb03985.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate‐Deficient Transferrin: Diagnostic Efficiency Among Patients with End‐Stage Liver Disease Before and After Liver Transplantation

Abstract: We tested the diagnostic validity of carbohydrate-deficient transferrin (CDT) as an indicator for relapse into elevated alcohol consumption among patients who were examined under follow-up treatment before (n = 147) and after (n = 102) orthotopic liver transplantation (OLT) in the outpatient-department of the University Hospital Department of Surgery in Hamburg-Eppendorf. CDT measurements were performed with two commercial kits in parallel (CDTect-RIA and CDT%-RIA). Short-term parameters of alcohol consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 22 publications
(1 reference statement)
0
31
0
Order By: Relevance
“…It generally decreases within 2 weeks of abstinence and will increase if persons resume drinking. 13,32,44 Quarterly testing of CDT levels in unstable diabetics or hypertensive patients may be indicated to monitor reductions or increases in drinking. CDT is the only alcohol biomarker sensitive enough to monitor reductions in alcohol use or relapse.…”
Section: Discussionmentioning
confidence: 99%
“…It generally decreases within 2 weeks of abstinence and will increase if persons resume drinking. 13,32,44 Quarterly testing of CDT levels in unstable diabetics or hypertensive patients may be indicated to monitor reductions or increases in drinking. CDT is the only alcohol biomarker sensitive enough to monitor reductions in alcohol use or relapse.…”
Section: Discussionmentioning
confidence: 99%
“…If these patients remain abstinent, their prognosis is superior to that of patients with liver cirrhosis of other etiologies. However, continued alcohol consumption is considered an absolute contraindication for LT. [1][2][3][4] Therefore, the high percentages of relapse cases before LT (19%-50%) 5,6 and after LT (11%-80%) [7][8][9][10][11][12][13][14][15][16][17][18][19][20] pose a serious problem. [21][22][23][24][25] To ensure abstinence by the patient, a strict and systematic investigation is required.…”
Section: See Editorial On Page 1267mentioning
confidence: 99%
“…Because of its short half-life and increased elimination in alcoholics, ethanol is also an unreliable method of testing. 8,[27][28][29] Since the 1980s, blood alcohol analysis has been established in forensic medicine for testing the blood levels of ethanol and other alcohols (eg, methanol, propanol-2, and acetone). Methanol is part of almost Abbreviations: ADH, alcohol dehydrogenase; ALC, alcoholic liver cirrhosis; LT, liver transplantation; SEC, serum ethanol concentration; SMC, serum methanol concentration; T0, time 0; T1, time 1; T2, time 2. every alcoholic beverage in different concentrations.…”
Section: See Editorial On Page 1267mentioning
confidence: 99%
“…exceeding 60 g of ethanol on most days) (Bergstrom and Helander, 2008). Despite its utility in identifying chronic heavy drinking, CDT assay methods have diminished specificity for heavy alcohol use in patients with liver disease and particularly cirrhosis (Heinemann et al, 1998;DiMartini et al, 2001). Case series using the relatively newer HPLC or capillary electrophoresis assays for %dCDT have shown that liver disease can be associated with a diminished chromatographic resolution of disialotransferrin from trisialotransferrin (Arndt et al, 2008;Stewart et al, 2010;Gonzalo et al, 2012), which is the likely cause of this diminished specificity for heavy drinking.…”
Section: Introductionmentioning
confidence: 99%